Spatiotemporal distribution of global peatland area during the Holocene - Hui Liu; Haibin Wu; Wenchao Zhang; Jie Yu; Junyan Geng; Xiuqin Le; Yanyan Yu (Scientific Data)
Abstract Peatlands are a key component of terrestrial ecosystems, and their development has an important impact on global carbon cycle and climate change. However, the long-term evolution of global peatlands remains uncertain, particularly their spatial distribution. We compiled 4700 basal peatland data during Holocene, and 669 pollen data of Sphagnum with basal and end ages, to allow a more robust reconstruction of the spatial distribution of peatlands. Using buffer analysis (BA) and inverse distance weighted (IDW) interpolation of peat data, we reconstructed spatiotemporal changes in global peatland area at a spatial resolution of 0.5° × 0.5° for every 1,000 years period during Holocene. The results show that peatland area have expanded substantially in North America, Europe, and Western Siberia during early-Holocene, and increased rapidly from 2.18(0.32) Mkm2 to 4.03(3.08) Mkm2 during 12-6 ka BP, then slowly to 4.15(4.23) Mkm2 after 6 ka BP according to BA (IDW) methods. The database will be useful for analyzing the global/regional terrestrial carbon cycle and climate change during Holocene, especially for modeling peatland methane emissions.